Yield and phosphorus use efficiency of carrot cultivars (Bioscience Journal, 2021)
Phosphate fertilization is indispensable for carrot cultivation, as it contributes to plant development, formation of marketable roots and higher yields. In this context, the objective of this study was to evaluate the production and nutritional efficiency of carrot cultivars under phosphate fertilization. The experiments were carried out from July to November 2016 and from June to October 2017, at the Rafael Fernandes experimental farm, District of Alagoinha, Mossoró, RN, Brazil. The experimental design was in randomized blocks, in a 4×4 factorial scheme with 4 replicates. The treatments consisted of the combination of carrot cultivars (Brasília, Planalto, Suprema and Nativa) with phosphorus (P) doses (0, 90, 180 and 270 kg ha-1 P2O5). The characteristics analyzed were: P content in the diagnostic leaf, plant dry matter, plant height, marketable and total yields, and the classification of cultivars for efficiency and response to phosphate fertilization. The increments promoted by phosphate fertilization were 64% in plant height, 444% in dry matter and 284% in marketable yield. The maximum marketable yield was obtained with doses from 186.8 to 243.5 kg ha-1, depending on the cultivar. The Native cultivar was classified as more efficient in the use of P.